Moderating effect of self-determination in the relationship between Big Five personality and academic performance. (November 2015) - Zhou, Mingming
Abstract: Previous studies have shown that both personality and motivation are important factors in student academic performance. This study examined how the interactions between the Big Five personality traits and self-determination motivation orientations affect students' academic performance. The hypotheses were empirically tested using cross-sectional data collected from 249 primary school students in China. The correlation analysis found that self-determined motivation and four of the five personality traits (not emotional instability) were significantly positively related to academic performance in English. The hierarchical regression analysis revealed that, after controlling for gender, openness to new experience and conscientiousness both positively predicted English performance. Significant interaction effects were found between agreeableness and self-determined motivation, and between conscientiousness and self-determined motivation. However, conscientiousness and agreeableness only positively predicted academic performance when the student's self-determined motivation was low. Highlights: Personality and motivation were examined in predicting academic performance. Self-determination and personality factors were positively related to performance. Significant interaction effect was found between agreeableness and self-determination. Significant interaction effect was found between conscientiousness and self-determination.